Effects of biophilic indoor environment on stress and anxiety recovery: A between-subjects experiment in virtual reality - Yin, Jie; Yuan, Jing; Arfaei, Nastaran; Catalano, Paul J.; Allen, Joseph G.; Spengler, John D. (Environment international, 2020)
•Biophilic environments had larger restorative impact than non-biophilic environment.•Biophilic environments reduced stress and anxiety.•Effects on physiological response are immediate after biophilic exposure.•Restorative effects differ among three different types of biophilic environments. Previous research has demonstrated the positive associations between outdoor nature contact and stress reduction. However, similar effects of incorporating natural elements into indoor environment (i.e. biophilic design) have been less well studied. We hypothesize that exposure to biophilic indoor environments help people recover from stress and anxiety and those effects differ among different types of biophilic elements. To test these hypotheses, we conducted a between-subjects experiment with 100 participants using virtual reality (VR). Participants were randomly assigned to experience one of four virtual offices (i.e. one non-biophilic base office and three similar offices enhanced with different biophilic design elements) after stressor tasks. Their physiological indicators of stress reaction, including heart rate variability, heart rate, skin conductance level and blood pressure, were measured by bio-monitoring sensors. Their anxiety level was measured by using State-Trait Anxiety Inventory test (short version). We found that participants in biophilic indoor environments had consistently better recovery responses after stressor compare to those in the non-biophilic environment, in terms of reduction on stress and anxiety. Effects on physiological responses are immediate after exposure to biophilic environments with the larger impacts in the first four minutes of the 6-minute recovery process. Additionally, these restorative effects differ among three different types of indoor biophilic environments. This research provides evidence that biophilic design elements that impact stress recovery and anxiety. It also demonstrated the potential that virtual reality may be a way to bring nature and its therapeutic benefits to patients in hospitals.